Analysis of Patient Satisfaction with Pharmaceutical Services at the Northern Region Primary Health Center of Kediri City in 2019 - Hanie Kusuma Wardan (Universitas STRADA Indonesia, 2019)
Pharmaceutical services are an integral component of the health care system at primary health center. One of the quality indicators in pharmaceutical services at the Northern Region Primary Health Center of Kediri City is patient satisfaction. This study aims to analyze patient satisfaction with pharmaceutical services at the Northern Region Primary Health Center of Kediri City in 2019. Using a cross-sectional design, the study involved 110 respondents selected through accidental sampling. Data were collected using a standard questionnaire from Regulation of the Minister of Health of the Republic of Indonesia No. 74 of 2016 and analyzed using the Community Satisfaction Index method. The results showed a Community Satisfaction Index value of 3.19 (equivalent to 79.66 after conversion), indicating a satisfaction level of